(untitled) (Journal SCIENCEVOLUTION, 2025)
The study evaluated the effect of biochar and fish hydrolysate as organic amendments for the recovery of saline soils in Yarada Los Palos, Tacna, Peru. An experimental investigation was conducted using a completely randomized design to assess the impact of these treatments on the soil’s physicochemical properties, including pH, electrical conductivity (EC), organic matter content, and germination index. Soil samples affected by salinity were collected and treated with biochar in combination with fish hydrolysate. Fish hydrolysate proved to be more effective, reducing electrical conductivity to 3.84 dS/m, stabilizing pH at 7.18, and increasing the germination index to 96.4%. It also improved porosity, moisture retention, and organic matter levels. These results demonstrate the potential of these amendments particularly fish hydrolysate as sustainable tools for the rehabilitation of salt-affected soils. It is recommended to use in arid or semi-arid regions, along with evaluation at a larger scale.